The Influence of Environmental, Social and Governance (ESG) Components on Debt Costs in Manufacturing Companies in Indonesia - Nilammadi, Wa Ode Musmiarny; Triani, Ni Nyoman Alit; Eni, Wuryani (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study aims to test and analyze the influence of environmental, social and governance components on debt costs. The subjects of the study were manufacturing sector companies listed on the IDX for the 2020-2023 period. This study uses a quantitative method using secondary data and processed using the SmartPLS application. The results of this study indicate that environmental, social and governance do not have a significant effect on debt costs. This study contributes both academically and practically. From an academic perspective, this study serves as a foundation for further research on environmental, social, governance and debt costs. From a practical perspective, companies have the opportunity to improve the quality and credibility of their corporate sustainability reports.